PROFIL USAHA OBJEK WISATA TRACKING MANGROVE DESA TRANS PATO’A KECAMATAN HELUMO KABUPATEN BOLAANG MONGONDOW SELATAN (Business Profile of Tracking Mangrove Tourism Objects in Trans Pato'a Village, Helumo District, South Bolaang Mongondow Regency) - Wiro Manileth; Gene H. M. Kapantow; Lyndon R. J. Pangemanan (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
Mangrove forest is one of the tourist attractions in North Sulawesi, including the Mangrove Forest in Trans Pato'a Village. This tourist spot, which is named "Tracking Mangrove Trans Pato'a Village" is located about 20 km from the South Bolaang Mongondow City Center, and can be reached in 45 minutes.This study aimed to determine the business profile of Mangrove Tracking in Trans Pato'a Village, Helumo District, South Bolaang Mongondow Regency. This research was conducted from August to October 2020. The data used in this study were primary data and secondary data. Primary data were taken by researchers directly in the field using a questionnaire. Secondary data were obtained through government agencies, and institutions related to this research. A total of 20 people were selected as respondents using the purposive sampling method. These respondents represent managers, visitors, and the local community.The results showed that accessibility, accommodation, hydrological conditions, supporting facilities, tourism object managers, and supporting infrastructure at the Mangrove Tracking tourism object in Trans Pato'a Village were in good condition.